Reviewing The OIC's Response And Challenges to The Issues of Normalization of Arab State – Israel Relation in The 2020-2021 Pandemic Era (Metaverse) - Zainal, Nur Aliyah; Andi Annur Aisyah (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
The normalization of relations between Arab countries and Israel in such a way has become a frightening specter for Palestine and also most of the Muslim community in the world, this issue of course raises a perception that the two countries that are said to be opening this cooperative relationship will in the future and eliminate the existence of Palestine, and also weakens the solidarity of Islamic countries towards the independence of Palestine, and does not rule out the possibility that other Islamic countries will also open up opportunities for cooperation with Israel. Therefore, as an Organization that supports international peace and security, the response or attitude of the Organization of Islamic Cooperation is felt to be urgently needed in order to revitalize the unity of the Islamic state in order to assist the struggle for the establishment of an independent and sovereign Palestinian state.